In search of home: an ethnographic case study exploring collaborative educational efforts addressing rural homelessness - Cochrane, Meaghan (Kansas State University, 2018)
Over the past five years, alone, in the rural state of West Virginia, the number of identified homeless students has increased 315%— from 2,000 students to 8,300 students— which is assumed to be a conservative estimate by local and state education officials (Mays, 2014). Homelessness is often identified as an urban problem, as the most visible forms occur among street dwellers in urban settings (Joyce-Beaulieu & Sulkowski, 2014). Within rural locations, however, homelessness predominately remains a concealed issue requiring extensive collaboration to combat issues of geographic isolation and lack of support, infrastructure, and public services. This study will demonstrate how community school programming offers considerable potential to provide direct support and services within the school setting for rural homeless youth.
Keywords: Community school; Rural; Homeless; Education; West Virginia